2020
DOI: 10.1017/cem.2020.446
|View full text |Cite|
|
Sign up to set email alerts
|

Burnout and depression among Canadian emergency physicians

Abstract: Burnout is a work-related syndrome involving emotional exhaustion, depersonalization, and a sense of reduced personal accomplishment. 1 In this issue of CJEM, Lim et al. 2 published a landmark study reporting burnout (as measured by the 22-item Maslach Inventory), depression (measured by PHQ-9), and suicidal thoughts among Canadian emergency physicians in 2019. This study is the first of its kind to measure the mental health and well-being of Canadian emergency physicians. The investigators are to be praised f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, an association analysis showed that burnout was significantly related to depression, a finding similar to that of a survey of emergency physicians. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an association analysis showed that burnout was significantly related to depression, a finding similar to that of a survey of emergency physicians. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Expectations for rapid high-quality emergency care while simultaneously boarding large numbers of inpatients who cannot access hospital beds and providing safety-net care for patients who cannot access primary or specialty care has stretched ED staff and capacity beyond their limits. The result is overcrowding, adverse outcomes, suboptimal patient experience and mental health consequences for healthcare workers [7,8].…”
mentioning
confidence: 99%